Catheter Directed Thrombolysis in the Treatment of Acute Pulmonary Embolism: Early Hemodynamic Recovery and Improvement in Prognosis. (24th March 2022) - Guan, Qinglong; Wang, Xiaofei; Liu, Chenglong; Gao, Yuan; Chen, Haibo; Li, Gang
Abstract : Aim . In this study, we aimed to investigate the efficacy of catheter directed thrombolysis (CDT) and peripheral intravenous thrombolysis (PIT) in the treatment of patients with acute pulmonary embolism (APE) and assess its effect on the prognosis of patients. Methods . We recruited 74 patients with APE, who were assigned to CDT and PIT groups, according to the treatments received by them. The arterial partial pressure of oxygen (PaO2 ), partial pressure of carbon dioxide (Pa CO2 ), pulmonary artery pressure (PAP), pulmonary artery obstruction index (PAOI), thrombus volume, pain score, and therapeutic benefits were compared between the two groups before and after treatment, and the factors affecting patient prognoses were also analyzed. Results . Using the clinical data before treatment as the baseline, it was found that changes in indicators of plasma, thrombus volume, and pain scores were significantly better in the CDT group than in the PIT group after treatment. The total effective rate of CDT was higher than that of PIT in the treatment of APE. The mean follow-up time for both the CDT and PIT groups was 41.08 ± 9.12 months, and the total mortality rate was 14.8% and 31%, respectively. The logistic regression analysis revealed the significant impacts of previous incidences of pulmonary embolism (PE), concurrent deep vein thrombosis (DVT), and pulmonary arterial hypertension (PAH) on the occurrence and progression of APE, and these factors were subsequently identified as risk factors for APE using Kaplan–Meier survival analysis. Observations from PAE onset to the end of follow-up revealed that there was a difference in survival rates between the CDT and PIT groups. Conclusions . Taken together, CDT is an effective treatment strategy for APE and can provide effective symptomatic relief. In addition, the previous incidences of PE, concurrent DVT, and PAH are important risk factors that affect the survival rates of patients with APE.